Combined Experimental and DFT Study of Alumina (α-Al2O3(0001))-Supported Fe Atoms in the Limit of a Single Atom - Ramazan T. Magkoev; Yong Men; Reza Behjatmanesh-Ardakani; Mohammadreza Elahifard; Ivan V. Silaev; Aleksandr P. Bliev; Nelli E. Pukhaeva; Anatolij M. Turiev; Vladislav B. Zaalishvili; Aleksandr A. Takaev; Tamerlan T. Magkoev; Ramazan A. Khekilaev; et al. (Nanomaterials)
To probe the properties of single atoms is a challenging task, especially from the experimental standpoint, due to sensitivity limits. Nevertheless, it is sometimes possible to achieve this by making corresponding choices and adjustments to the experimental technique and sample under investigation. In the present case, the absolute value of the electronic charge the Fe atoms acquire when they are adsorbed on the surface of aluminum oxide α-Al2O3(0001) was measured by a set of surface-sensitive techniques: low-energy ion scattering (LEIS), Auger electron spectroscopy (AES), low-energy electron diffraction (LEED), and work function (WF) measurements, in combination with density functional theory (DFT) calculations. The main focus was the submonolayer coverage of Fe atoms in situ deposited on the well-ordered stoichiometric α-Al2O3(0001) 7 nm thick film formed on a Mo(110) crystal face. An analysis of the evolution of the Fe LVV Auger triplet upon variation of the Fe coverage shows that there is electronic charge transfer from Fe to alumina and that its value gradually decreases as the Fe coverage grows. The same trend is also predicted by the DFT results. Extrapolation of the experimental Fe charge value versus coverage plot yields an estimated value of a single Fe atom adsorbed on α-Al2O3(0001) of 0.98e (electron charge units), which is in reasonable agreement with the calculated value (+1.15e). The knowledge of this value and the possibility of its adjustment may be important points for the development and tuning of modern sub-nanometer-scale technologies of diverse applied relevance and can contribute to a more complete justification and selection of the corresponding theoretical models.